2016
DOI: 10.1177/0956797616677314
|View full text |Cite
|
Sign up to set email alerts
|

Logged In and Zoned Out

Abstract: Laptop computers are widely prevalent in university classrooms. Although laptops are a valuable tool, they offer access to a distracting temptation: the Internet. In the study reported here, we assessed the relationship between classroom performance and actual Internet usage for academic and nonacademic purposes. Students who were enrolled in an introductory psychology course logged into a proxy server that monitored their online activity during class. Past research relied on self-report, but the current metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 26 publications
5
51
0
5
Order By: Relevance
“…They do not establish that it is the division of attention in class that causes the poorer performance. These results (Fried, 2008;Jacobsen & Forste, 2011;Junco, 2012;Kraushaar & Novak, 2010;Ravizza et al, 2014Ravizza et al, , 2017 cannot rule out the plausible hypothesis that the students who are more likely to divide attention between academic and non-academic tasks in class are also more likely to do so out of class. So generally, less attention to study both in and out of class ultimately reduces exam performance rather than a specific effect of divided attention on classroom learning.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…They do not establish that it is the division of attention in class that causes the poorer performance. These results (Fried, 2008;Jacobsen & Forste, 2011;Junco, 2012;Kraushaar & Novak, 2010;Ravizza et al, 2014Ravizza et al, , 2017 cannot rule out the plausible hypothesis that the students who are more likely to divide attention between academic and non-academic tasks in class are also more likely to do so out of class. So generally, less attention to study both in and out of class ultimately reduces exam performance rather than a specific effect of divided attention on classroom learning.…”
Section: Introductionmentioning
confidence: 93%
“…So, when students divide attention between an electronic device and the classroom lesson they should be learning less. In fact, several classroom studies have found a negative correlation between the amount of time spent using an electronic device for non-academic purposes during class and subsequent exam performance using both self-report measures of electronic device use (Fried, 2008;Jacobsen & Forste, 2011;Junco, 2012;Ravizza, Hambrick, & Fenn, 2014) and direct electronic monitoring (Kraushaar & Novak, 2010;Ravizza, Uitvlugt, & Fenn, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2012, 96% of 15-year-old students in OECD (Organisation for Economic Co-operation and Development) countries stated that they had a computer at home, and 72% said they used a digital device at school. More and more studies show that the use of technology and digital devices in the classroom does not directly correlate to improvements in students' academic results and can have a negative effect on their educational performance [4]. It has been shown that students who use computers at school in moderation and strictly for educational purposes achieve better results than students who hardly ever use them, but if computer use is more pronounced, the results in reading, maths, and the sciences worsen across all OECD countries regardless of the students' socio-educational Sustainability 2020, 12, 749 2 of 15 context [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although multitasking is not a new phenomenon, its frequency has increased markedly due to the pervasiveness and ubiquity of digital technologies (Wood & Zivcakova, 2015). Against this backdrop, laptops and phones are shown to be the major source of distraction for students (Hembrooke & Gay, 2003;Rosen et al, 2013); hence there has been increasing concern over the disruptive force of computers and smart phones and their effect on student memory, concentration, and learning performance (e.g., Junco & Cotten, 2012;Patterson, 2017;Ravizza, Uitvlugt, & Fenn, 2017;Wood et al, 2012). However, our understanding of the nature of interruption from mobile phones and computers and the process of the ensuing task switching is far from conclusive.…”
Section: Introductionmentioning
confidence: 99%